Nematodes infecting Phyllopezus pollicaris (Spix, 1825) (Reptilia: Phyllodactylidae) in the Palmares National Forest, Piauí State, Brazil - Costa, Brenda Milena Bezerra (2025)
Parasitological studies are important to understand the host-parasite interaction, providing information on the coevolution, biogeography, morphology, and diet of the species. The present study describes the endoparasite fauna of the lizard Phyllopezus pollicaris (Spix, 1825) in the Palmares National Forest, Piauí State, Brazil, a tropical forest covered by transitional vegetation between the Caatinga and Cerrado biomes. Furthermore, we investigated the influence of lizards’ size and sex on endoparasite infection patterns. We analyzed 23 individuals of P. pollicaris, of which 18 were infected by at least one helminth, belonging to the Nematoda phylum: Spauligodon oxkutzcabiensis (Chitwood, 1938), Strongyloides sp., and Parapharyngodon sp. Overall, S. oxkutzcabiensis showed the highest prevalence (73.9%), mean infection intensity (8.64 ± 12.7), and mean abundance (6.39 ± 11.5). We observed that the lizard size was positively related to the abundance of endoparasites, while the sex of individuals had a poor effect on parasitological descriptors.This study contributes information about the endoparasite fauna associated with P. pollicaris, composed exclusively of nematodes. As a pioneering study, it can be considered the starting point for parasitological studies involving lizards in Piauí State, Northeastern Brazil.